Combining ability in fennel (Foeniculum vulgare Mill.) for yield and quality - Raje, S S Rajput, D L Singhania, D Singh, R S (Journal of Spices and Aromatic Crops, 2005)
Twelve genetically diverse varieties of fennel (Foeniculum vulgare) were evaluated at Jobner (Rajasthan) following diallel mating design for determining their utility as parents in the development of hybrids and/or high yielding composites. The analysis of variance indicated that varieties and heterosis were significant for most of the characters studied, indicating complex type of inheritance involving additive, dominance and epistatic components. The heterosis sum of squares accounted for more than 75% of the entries sum of squares. Partitioning of overall heterosis variation indicated that contribution of specific heterosis was the highest (>50%) among the three components. Estimates of genetic constants indicated that varietal heterosis effects were significa nt for all the tra its except days to 50% flowering and test weight, while specific heterosis effects were significant for most of the characters. The cross RF-101 x JF-25 showed the highest positive specific heterosis effect for seed yield plant·, along with high specific heterosis effects for umbels and biological yield plan 1’’. These two parents represented a good choice to initiate inter-population improvement.